Phylogeny and Population Genetic Structure of Minke Whales Worldwide : A Review of Recent Studies - Pastene, Luis A. A. (2019)
In 1998, two species of minke whales were recognized based on the review of the morphological and genetic information available at that time: the Antarctic minke whale (Balaenoptera bonaerensis), which is restricted to the Southern Hemisphere, and the cosmopolitan common minke whale (Balaenoptera acutorostrata). Furthermore, three sub-species of the common minke whale were recognized: the North Atlantic (B. a. acutorostrata), North Pacific (B. a. scammoni) and Southern Hemisphere (B. a. subsp.). This chapter reviews the genetic studies on minke whales conducted after 1998. The review is organized by topic, e.g., those studies focused on phylogeny and other matters most relevant for taxonomy, and those focused on population genetic structure within oceanic basins most relevant for conservation and management. On the former topic, the new genetic information, whilst strongly supporting the minke whale taxonomic classification recognized in 1998, also reveals substantial genetic differentiation within the Southern Hemisphere common minke whales, with subsequent taxonomic implications. On the latter topic, results from different analytical procedures have provided information on population identification and structure in the Indo-Pacific sector of the Antarctic and western North Pacific, but they have failed to identify unequivocally any population within the North Atlantic common minke whales.